EFFECTIVENESS OF PROJECT BASED LEARNING ON MATHEMATICAL CRITICAL THINKING ABILITY STUDENTS ON QUADRATURE FUNCTIONS IN CLASS X - Silaban, Naomi; Situmorang, Adi Suarman; Tambunan, Hardi; Manik, Efron; Gultom, Sanggam P (Dharmas Education Journal (DE_Journal), 2021)
This study aims to determine the effectiveness of project-based learning on mathematical critical thinking skills in the quadratic function material of class X of St. Paul's Private High School T.A 2024/2025. The type of research used is quantitative descriptive. The research population is all class X and the research sample consists of 64 students of class X. The sampling technique is carried out by random sampling technique. The instruments used are tests in the form of description questions, questionnaires and observation sheets. The results of the study are seen from the indicators of effectiveness that are met, namely the systematics of learning in the good category, the communication of the teacher in the good category, the response of the students in the good category, the activities of the students in the good category, and the achievement of learning in the category is achieved. The results of the study show that project-based learning is effective on students' mathematical critical thinking skills.